This vital air, this vital water man's environmental crisis - Aylesworth, Thomas G. (Chicago Rand McNally, 1973)
Presents the facts about air, water, and noise pollution, focusing on causes and effects, methods of control, the role of science and research, and hope for the future.
Bibliography: p. 181-182.
Keywords: Air -- Pollution -- Juvenile literature; Water -- Pollution -- Juvenile literature; Noise control -- Juvenile literature; Air -- Pollution; Water -- Pollution; Noise pollution